2013
DOI: 10.1039/c3cc46193a
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular arylation of amino acid enolates

Abstract: Dianionic enolates formed from N'-aryl urea derivatives of amino acids undergo intramolecular C-arylation by attack of the enolate anion on the N'-aryl ring, leading to a hydantoin derivative of a quaternary amino acid. In situ IR studies allow identification of four intermediates on the reaction pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 53 publications
0
35
0
2
Order By: Relevance
“…Angewandte metadynamics and committor analysis methods have been studied by Moors et al [52] They found that for 4-nitrofluorobenzene (74), the reaction proceeded via ac oncerted mechanism in the gas phase via transition state 77,b ut via an intermediate Meisenheimer complex 83 in solution (Schemes 17 and 18). For4 -nitrochlorobenzene (75), the reaction proceeded via aconcerted mechanism via transition state 78 in both the gas phase and in solution, and for 2,4dinitrofluorobenzene (76), the reaction occurs via aM eisenheimer intermediate 79 in both solution and the gas phase.…”
Section: Methodsmentioning
confidence: 99%
“…Angewandte metadynamics and committor analysis methods have been studied by Moors et al [52] They found that for 4-nitrofluorobenzene (74), the reaction proceeded via ac oncerted mechanism in the gas phase via transition state 77,b ut via an intermediate Meisenheimer complex 83 in solution (Schemes 17 and 18). For4 -nitrochlorobenzene (75), the reaction proceeded via aconcerted mechanism via transition state 78 in both the gas phase and in solution, and for 2,4dinitrofluorobenzene (76), the reaction occurs via aM eisenheimer intermediate 79 in both solution and the gas phase.…”
Section: Methodsmentioning
confidence: 99%
“…The Clayden rearrangement suggests a direct route to α‐arylated non‐natural amino acids using amino acid derived ureas 125 . However, the direct transformation of ureas to these valuable products was complicated by hydantoin ( 126 ) formation following aryl migration of amino acid enolates (Scheme ) . Use of an N ‐(4‐methoxybenzyl) protecting group provided a route to the desired amino acid derivatives, through oxidative deprotection and hydrolysis of the hydantoin.…”
Section: Two‐electron Smiles Rearrangementmentioning
confidence: 99%
“…Attempts to extend the scope of this reaction prompted Clayden and coworkers to address the challenge of applying this anionic arylation to the enolates of amino acid derivatives (Scheme 32). 58 A series of natural and unnatural amino acids were derivatized as ureas, treated under optimized conditions, and quenched with dilute HCl to give racemic hydantoins. For a range of amino acid derivatives, with a variety of migrating aryl (including pyridyl) rings, arylation took place cleanly.…”
Section: Arylation Of Estersmentioning
confidence: 99%